Description of the mature larva of Pseudopyrochroa depressa (Pic) (Coleoptera: Pyrochroidae: Pyrochroinae), with comparison to other Taiwanese Pseudopyrochroa - Young, Daniel K.; Hsiao, Yun (Zootaxa, 2016)
Field collections and rearing has established an association between the larva and adult of the Taiwanese Pseudopyrochroa depressa. Larvae were collected from beneath bark of the exposed portions of a dead, decaying log in a mesic montane forest and successfully reared to the adult stage. The mature larva is described and salient features are illustrated and compared to other known pyrochroid larvae from Taiwan. Notes on larval habitats and natural history are also provided.